Green Starch Modification Using Citric Acid: Quinoa, Chickpea, and Cassava Starches - Disala Menuwara Arachchi; Anthony Halim; Gbemisola Fadimu; Asgar Farahnaky; Mahsa Majzoobi (Foods)
Dietary fibre deficiency has been associated with various global health challenges. Starch, as a main component of many staple foods, is typically very low in fibre content. The primary aim of this research was to increase the dietary fibre and alter the physicochemical properties of some common and emerging starches (cassava, quinoa, and chickpea starch) using eco-friendly modifications. Citric acid, a safe, natural, and environmentally friendly cross-linking agent, was employed for this purpose. Starch samples were treated with 30% citric acid and dry-heated at 130 °C for 5 h. This process resulted in relatively high degrees of substitution: 0.124 for cassava, 0.117 for quinoa, and 0.112 for chickpea starches. The modification successfully produced rich sources of dietary fibre suitable for food applications. It also reduced water interactions, pasting properties, and crystallinity. The highest reduction in swelling power and solubility was observed in quinoa starch (−67.34% and −82.10%, respectively), while the lowest values were obtained for cassava starch (−35.39% and −44.22%). All starches retained their granular integrity; however, they lost birefringence and Maltese crosses and showed some erosions on the granule surfaces. The citrate starches produced in this research offer thermally stable starch suitable for various food applications.